2022
DOI: 10.26444/aaem/149963
|View full text |Cite
|
Sign up to set email alerts
|

Differences in microbiological quality of leafy green vegetables

Abstract: Objective. The aim of the study was to determine the presence and concentration of indicator microorganisms on leafy green vegetables available in Poland. Material and methods. Microbial analyses of 122 samples of leafy green vegetables: rocket, lamb's lettuce, iceberg lettuce, chive, spinach, celery, dill and parsley, sold in Polish supermarkets in 2018 and 2019, were conducted. The vegetables were analyzed for aerobic mesophilic bacteria, yeasts and moulds, Enterobacteriaceae, Enterococcus, coliforms and Esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…The other dominant group of microorganisms were yeasts. According to Kowalska and Szczech [36] their number in iceberg lettuce ranged from 3.4 to 4.0 log10 cfu g -1 , while in other leafy greens the value was higher -about 6.0 log10 cfu g -1 , and these findings are in accordance with presented data. In the case of molds, their number increased during storage especially in control lettuce.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The other dominant group of microorganisms were yeasts. According to Kowalska and Szczech [36] their number in iceberg lettuce ranged from 3.4 to 4.0 log10 cfu g -1 , while in other leafy greens the value was higher -about 6.0 log10 cfu g -1 , and these findings are in accordance with presented data. In the case of molds, their number increased during storage especially in control lettuce.…”
Section: Discussionsupporting
confidence: 89%
“…Jackson et al [41] have found that total cultured bacteria in lettuce and spinach, stored in modified chilled atmosphere increased to 5.5 x 10 8 cfu g -1 . Kowalska and Szczech [36] reported that in leafy vegetables sold in supermarkets, the mesophilic bacteria was the dominant group in all products and reached values as high as 8.4 log10 cfu g -1 , and for iceberg lettuce the bacterial load ranged from 2.08 to 7.16 log10 cfu g -1 . Similarly Sun et al [42] have found that after storage for 3 days the number of bacteria in lettuce increased more than 5 log10 cfu g -1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because these microorganisms change and accelerate the aging process of stored flowers and can produce volatile compounds responsible for off-flavours and texture changes [Rawat, 2015]. The presence of moulds and yeasts is also undesirable due to their potential adverse effects on human health -some of them (Aspergillus, Penicillium, Alternaria or Fusarium) may produce mycotoxins and others may cause allergies (Cladosporium, Alternaria) [Habibi Najafi & Bahreini, 2012; Kowalska & Szczech, 2022;Tournas, 2005].…”
Section: Resultsmentioning
confidence: 99%
“…According to Kowalska and Szczech [81], assessing the microbiological contamination of vegetables includes determining the levels of Gram-negative bacteria of the Enterobacteriaceae family, with particular relevance to fecal Enterobacteriaceae as general indicators of pollution. The RSA [78] determines that the upper limit value of the microbiological count below which ready-to-eat foods do not represent a health risk corresponds to 5.69 log CFU g −1 .…”
Section: Effect Of Intensity and Photoperiod On Microbiological Countsmentioning
confidence: 99%